The Victimizer of Good Will: Anxiety, Denial, and Guilt in the Television Serial Parashat Ha-Shavu’a - Harlap, Itay (MiKAN, 2013)
The article examines the character of Shaul Nawi in the first season of the Israeli television serial Parashat Ha-Shavu’a (2006). It argues that Shaul’s distress, which takes the form of extreme mood swings, anxiety, and post-traumatic symptoms, is intimately linked to the various subject positions he occupies: a victim, a victimizer, and a bystander who witnesses wrongful acts perpetrated by and against others. The article discusses these multiple positions as they manifest themselves in Shaul’s extreme reaction at the sight of a dead soldier. It argues that this is related in the series to the fact that Shaul, like all Israeli citizens, is unavoidably responsible for what takes place in the Occupied Territories, even if he himself refuses to take part in the occupation and is himself a victim in other circumstances.